Proposed construction and completion one unit of stall for Majlis Daerah Tampin / Mohammad Amierul Aiman Azmie - Azmie, Mohammad Amierul Aiman (Universiti Teknologi Mara, Perak, 2016)
Majlis Daerah Tampin is name of a local council or local authority. Negeri Sembilan Darul Khusus have 5 local council such as Majlis Daerah Jelebu, Majlis Daerah Jempol, Majlis Daerah Kuala Pilah, Majlis Daerah Rembau, and Majlis Daerah Tampin. Majlis Daerah Tampin cover area such as Tampin, Repah, Gemencheh, Batang Melaka, Air Kuning and Gemas. Majlis Daerah Tampin have guideline and follow act and by-laws.